Lingkungan di Jakarta dan Kota Sekitar: Apakah Mandiri? - Wiranegara, Hanny Wahidin; Supriatna, Yayat; Sihombing, Pardomuan Robinson; Gunawan, Ghina Hanifa; Ramadhisa Fadli, Diva Aisyaliani; Sodiqin, Achmad (Jurnal Sosioteknologi, 2025)
Urban areas struggle with inefficient mobility, uneven facility distribution, and declining quality of life. The concepts of self-contained neighborhoods and the 15-minute city offer solutions by promoting access to essential services within a 15-minute walk. Nevertheless, empirical studies in fast-growing metropolitan cities in Jabodetabek remain limited, despite their vulnerability to urban sprawl, spatial fragmentation, and unequal access. This study examines residential neighborhoods in the Jabodetabek cities through a household survey that measures walking times to 42 types of facilities, calculated using Google Maps. Data were analyzed using the Kolmogorov-Smirnov test and a one-sample t-test against the 15-minute benchmark. Results show an average walking time of 16.35 minutes (SD = 4.18), exceeding the target. Basic services like minimarkets, primary schools, mosques, pharmacies, and community halls are accessible within 10 minutes, while non-basic services—including recreation, education, finance, and minority worship—require over 20 minutes. These findings indicate that the surveyed neighborhoods only partially fulfill the self-contained principle. The results are consistent with prior studies highlighting that metropolitan regions face difficulties in implementing the 15-minute city due to spatial imbalances and limited pedestrian infrastructure. In conclusion, residential neighborhoods in Jabodetabek cities have not yet fully achieved the criteria of self-contained neighborhoods. Policy directions should therefore focus on redistributing non-basic facilities, improving safe and comfortable pedestrian infrastructure, and promoting mixed-use development integrated with transit-oriented development (TOD) to reduce reliance on motorized vehicles and enhance urban quality of life.